2019
DOI: 10.1155/2019/6212673
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antimicrobial Activity of Extracts of Indigenous Wild Mushrooms against Pathogenic Organisms

Abstract: Objective. This study has investigated the antimicrobial activity of extracts of indigenous wild mushrooms against selected organisms. Methods. Thirty-five (35) indigenous wild mushrooms were collected from Arabuko-Sokoke and Kakamega National Reserve Forests, Kenya. All mushrooms were identified and their contents were extracted and screened for their antimicrobial activities against Escherichia coli (clinical isolate), Klebsiella pneumoniae (ATCC 13883), Pseudomonas aeruginosa (clinical isolate), Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 22 publications
1
51
3
1
Order By: Relevance
“…vernicipes is recommended by traditional healers to treat opportunistic infections, in immunocompetent individual such HIV positive patients. Previously, some studies have reported the antibacterial [12] and antioxidant [13] effects of this plant, but have not been evaluated its effect over the immune system. This work aimed to evaluate the immunomodulatory effect of the crude polysaccharides (PHW and PCW) from M. vernicipes over peritoneal neutrophil and macrophage functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vernicipes is recommended by traditional healers to treat opportunistic infections, in immunocompetent individual such HIV positive patients. Previously, some studies have reported the antibacterial [12] and antioxidant [13] effects of this plant, but have not been evaluated its effect over the immune system. This work aimed to evaluate the immunomodulatory effect of the crude polysaccharides (PHW and PCW) from M. vernicipes over peritoneal neutrophil and macrophage functions.…”
Section: Discussionmentioning
confidence: 99%
“…Microporus vernicipes belongs to the Polyporales family and distributes in the tropical and subtropical zone including Cameroon [11]. It has previously demonstrated that the water extract of Microporus vernicipes can have multiple activities such as antibacterial [12] and antioxidant [13] effects. It is traditionally used in treatment of opportunistic infections, whose normally absents in immunocompetent individual.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 20 exhibited moderate cytotoxicity against A-549 cells with an IC 50 value of 21.0 µM [98]. In addition to a new menthane monoterpene, 4-hydroxy-4-isopropenylcyclohexanemethanol acetate (22), craterellins D (23) and E (24) were later isolated from fungal cultures after minor modifications of the original cultural conditions. The cytotoxic activities of these compounds on five tumor cell lines were also reported [99].…”
Section: Cantharellus Cibarius Frmentioning
confidence: 99%
“…Friedman, et al reviewed mushroom polysaccharides which have shown therapeutic properties such as anti-obesity, anti-diabetes, anticancer and antibiotic properties [21]. Mushrooms endowed with potent antimicrobial and antioxidant properties, among other important bioactivities, have been reported in several studies [6,18,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms are immensely rich in bioactive compounds yet largely untapped resource of useful natural compounds. These bioactive compounds are found in various cellular components and secondary metabolites, which have been isolated and identified from the fruiting bodies [43]. Mushrooms have many biological activities thanks to these bioactive compounds [39].…”
Section: "#$%And!:(!)-;mentioning
confidence: 99%